Molecular identification and structural detection of anti-cancer compound from marine Streptomyces akiyoshiensis GRG 6 (KY457710) against MCF-7 breast cancer cells - Govindan Nadar Rajivgandhi; Govindan Ramachandran; Jia-Ling Li; Lingzi Yin; Natesan Manoharan; Moorthy Rajesh Kannan; Arockiam Antony Joseph Velanganni; Naiyf S. Alharbi; Shine Kadaikunnan; Jamal M. Khaled; Wen-Jun Li (Journal of King Saud University: Science, 2020)
The current study was concentrated to detection of anti-cancer compound from marine Streptomyces akiyoshiensis GRG 6 (KY457710) against MCF-7 breast cancer cells. The partial purification of TLC was moved three different active spots. Among the spots, the third spot of the extract was shown excellent anti-cancer properties against MCF-7 human breast cancer cells. The available anti-cancer compounds present in the partially purified extract was confirmed by GC–MS data interpretation. Three fractions of the compounds were purified by preparative HPLC and their respective spectrum was confirmed by analytical HPLC. Active anti-cancer fraction was separately purified by preparative HPLC and the cytotoxicity result was shown with 100 µg/mL concentration. The anti-cancer compound of pyrrolo [1,2-a]pyrazine-1,4-dione, hexahydro-3 was detected by LC-MS analysis after interpretation with GC–MS data. Further, the morphological damages and increased proliferation with more death cells of pyrrolo[1,2-a]pyrazine-1,4-dione, hexahydro-3 treated MCF-7 were observed by phase contrast and fluorescence microscope techniques. Finally, the nuclear condensation and increased necrotic cells of the pyrrolo[1,2-a]pyrazine-1,4-dione, hexahydro-3 treated MCF-7 cells was clearly identified by fluorescence microscope techniques using Hoechst 33,342 stain. Therefore, our result was prove, the pyrrolo[1,2-a]pyrazine-1,4-dione, hexahydro-3 rich Streptomyces akiyoshiensis GRG 6 (KY457710) as a potential anti-cancer agent against MCF-7 breast cancer cells.